The Concept of Time In Paul Tillich - Ali , Hassan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research seeks to clarify the concept of time of existential philosopher and theologian Paul Tillich, as philosophers who looked to time subjectivity an irrationality to complement the imitate Platonism and Augustinians, making time for a given part of eternity, and under its auspices, and that therefore everything is objective and rational is false, the greatest minds cannot understand the essence of time and what it is not, within the framework of a particular aspect of the time, while the simplest minds can be understood his secret and in living, and thus cannot understand time mentally But self-inflicted. That philosophy of Existentialism restore everything to the self, and the religious situation in general and Protestantism in particular also make case the faith as individual case special and unique, and then the self-time needs to undergo a qualitative eternal concept that sees the Tillich faith humane image of an existential nature, so it connects Tillich present time eternity, which are resurrected from the inside of the historical time, compelling all that is negative in being, which in the past is gone, and in the future on the end of man, and here show several questions such as, what is the nature of eternal? What is the present and the temporal and the eternal present? What is the kairos? In this research, we will try to answer those questions and other questions that will appear in the context of research